Risk factors for extubation failure in mechanically ventilated children in pediatric intensive care unit - Khurana, Supreet; Bhargava, Siddharth; Pooni, Puneet A; Bhat, Deepak; Dhooria, Gurdeep; Goraya, Jatinder; Arora, Kamaldeep; Kakkar, Shruti (Indian Journal of Child Health, 2019)
Background: Mechanical ventilation is lifesaving in children with respiratory failure. However, its unnecessary prolongation once a child is capable of sustaining spontaneous effective ventilation is associated with significant complications. Objective: To identify the factors that lead to higher chance of extubation failure in mechanically ventilated children. Materials and Methods: A prospective, observational study was conducted over a period of 1 year. Children admitted to pediatric intensive care unit of a tertiary care hospital of Northern India aged 1 month–17 years, needing mechanical ventilation were included in the study. Predefined criteria were used to decide the timing of extubation. Relevant details were recorded to study various patient-related parameters and their association with extubation outcome. Results: Mean age of the study group was 50 months with a male:female ratio of 3:1. Extubation failure rate was 14.5%. Extubation failure was significantly higher in patients ventilated for >7 days (p=0.01), those with the pediatric risk of mortality score >10 at admission (p=0.009), in addition to peak inspiratory pressure >16 cm H2O (p=0.009) and FiO2 ?0.35 (p=0.01) before extubation. Accidental extubation was also associated with higher extubation failure (p